ANALISIS PENGARUH SIKAP KONSUMEN DAN NORMA SUBYEKTIF ATAS PELAYANAN TERHADAP NIAT MELAKUKAN PEMBELIAN ULANG PADA PERUSAHAAN FORWARDING - Wilujeng, Ita Prihatining (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2008)
In line with expanding of forwarding business, there are new companies established. Whereas their service remain the same but the quality of delivering service usually different. It caused the changing of customer from one provider of service to others easily. Hence to be able to emulate it the company should offer the best service and must different from others. Especial attentions of company have to be addressed by effort how to create trust of customer to brand or product/service that they offer. Â It will escalate customer intention to do repeat buying. This research aim knows the influence of customer attitude and subjective norm to intention do repeat buying of service. The samples of this research are corporate which used of expedition service. To find out the influence of consumer attitude and subjective norm to intention do repeat buying utilizes regression analysis. The outcome of this research indicate that consumer attitude and subjective norm significantly influence of intention do repeat buying. While consumer attitude has the most dominant variable which is influence to intention do repeat buying.